The Prevalence and Clinical Implications of Rectal SARS-CoV-2 Shedding in Danish COVID-19 Patients and the General Population - Holm-Jacobsen, Julie Niemann; Bundgaard-Nielsen, Caspar; Rold, Louise Søndergaard; Jensen, Ann-Maria; Shakar, Shakil; Ludwig, Marc; Kirk, Karina Frahm; Donneborg, Mette Line; Vonasek, Julia Helena; Pedersen, Benjamin; Arenholt, Louise Thomsen Schmidt; Hagstrøm, Søren; et al. (Frontiers in Medicine, 2022)
Background: SARS-CoV-2 has resulted in a global pandemic since its outbreak in Wuhan, 2019. Virus transmission primarily occurs through close contact, respiratory droplets, and aerosol particles. However, since SARS-CoV-2 has been detected in fecal and rectal samples from infected individuals, the fecal-oral route has been suggested as another potential route of transmission. This study aimed to investigate the prevalence and clinical implications of rectal SARS-CoV-2 shedding in Danish COVID-19 patients. Methods: Hospitalized and non-hospitalized adults and children who were recently tested with a pharyngeal COVID-19 test, were included in the study. A rectal swab was collected from all participants. Hospitalized adults and COVID-19 positive children were followed with both pharyngeal and rectal swabs until two consecutive negative results were obtained. RT-qPCR targeting the envelope gene was used to detect SARS-CoV-2 in the samples. Demographic, medical, and biochemical information was obtained through questionnaires and medical records. Results: 28 of 52 (53.8 %) COVID-19 positive adults and children were positive for SARS-CoV-2 in rectal swabs. Seven of the rectal positive participants were followed for more than six days. Two of these (28.6 %) continued to test positive in their rectal swabs for up to 29 days after the pharyngeal swabs had turned negative. Hospitalized rectal positive and rectal negative adults were comparable regarding demographic, medical, and biochemical information. Furthermore, no difference was observed in the severity of the disease among the two groups. Conclusions: We provided evidence of rectal SARS-CoV-2 shedding in Danish COVID-19 patients. The clinical importance of rectal SARS-CoV-2 shedding appears to be minimal.